The effects of adapted mind-body exercises on physical function, quality of life and wellbeing for older people: a systematic review and meta-analysis - Lesley-Anne Tanhamira; Gurch Randhawa; David Hewson (Elsevier, 2024)
Background: Participating in physical activity programmes is one way to optimise wellbeing and quality of life in older adults. Mind-body exercises could provide greater benefits than other forms of traditional physical activity and can be easily adapted for older people who are starting to develop functional decline. Objectives: To synthesise the literature looking at the effects of adapted mind-body interventions on older people. Design: A systematic review and meta-analysis was conducted on articles from Web of Science, MEDLINE, SPORTDiscus, AMED and CINAHL that were searched up to 13 September 2023. Studies were extracted and assessed by two authors and included if they were adapted mind-body quasi experimental trials (QET) or randomised controlled trials (RCT) evaluating physical function, quality of life or wellbeing in community dwelling older adults aged 60 years and over. The Cochrane Risk of Bias 2 scale was used for quality appraisal. Analysis of the results included calculating standardised effect sizes (Hedge's g) and a narrative synthesis of results not included in meta-analysis. Results: 18 studies (8 quasi-experimental trial designs, n = 310; 10 randomised control trials, n = 1829) were included in the systematic review, with 14 studies (9 RCT, n = 1776, 5 QET, n = 100) retained for meta-analysis. For the RCT studies, some improvement was noted in mobility (ES 0.36: 95% CI: 0.01, 0.71), flexibility (ES 0.36: 0.01, 0.70), well-being (ES 0.54: 0.18, 0.91) and quality of life (ES 0.50: 0.21, 0.79). No positive effect was observed for leg power (ES 0.09: −0.33, 0.51), leg endurance (ES 0.16: −0.72, 1.03), back scratch test (ES 0.24: −0.10, 0.59), or balance, (ES 0.05: −0.06, 0.15). Heterogeneity varied from 0%-87% across the different outcomes. For the QET studies, gait velocity was shown to improve (ES 0.54: 0.18, 0.91), while fear of falling showed no significant improvements (ES 0.82: −0.06, 1.69). A meta-regression for quality of life in which the total physical activity of the intervention, in hours, was used as a covariate, showed ES = 1.1 for every 100 h of physical activity. Conclusion: There is scope for adapted mind-body physical activity interventions to play a role in improving quality of life, wellbeing, and physical function in older adults. The provision of adapted interventions for older people might improve uptake of and engagement with physical activity interventions in older people with limited or reduced abilities.